Strengthening for Entrepreneurship Program of Sorghum Base as Food Alternative During the Pandemic Recovery Covid-19 - Endang Noerhartati; Che Zalina Zulkifli; Pratiwi Dwi Karyati; Nugrahini Susantinah Wisnujati; Iva Evry Robiyansah; Nia Saurina; Lusy Tunik Muharlisiani (LPPM of NAROTAMA UNIVERSITY, 2020)
The purpose of this research was to find a solution during the pandemic recovery covid-19 with the strengthening of alternative food entrepreneurship sorghum. The research method uses qualitative research methods in entrepreneurship, descriptive qualitative action research with data collection techniques in the form of observation and documentation, after the data collected is then analyzed statistically descriptive. The results showed that sorghum can be used as a national food stock facing a crisis and pandemic covid-19, sorghum food stock in the form of grains, rice, flour, soft brand sorghum, and various processed sorghum. National sorghum food stock strategy includes strengthening clusters and production centers, silo utilization cooperation, socialization of various sorghum products, and strengthening Center of Sorghum Entrepreneur (CSE) and Sorghum Entrepreneurship Unit (SEU).